(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the structure and essence of foreign language communicative competence, as well as an innovative approach to the formation of foreign language communicative competences, the effective use of English works of art to prepare future English language teachers for effective intercultural communication